The Effect of Feed Restriction Programs and Growth Curves on Reproductive Performance, in vitro Lipogenesis and Heterophil to Lymphocyte Ratios in Broiler Breeder Hens - Beer, M. de; Coon, C.N. (International Journal of Poultry Science, 2009)
An experiment was conducted to compare Everyday (ED) and Skip-a-day (SK) feeding programs and early Slow growth (SLOW) and Broilerized (BROIL) treatments. Feed restriction programs were implemented from 4 weeks to 5% production. The SLOW group was fed to reach 75% of standard BW by 12 weeks and then to reach standard BW by 21 weeks. The BROIL group was fed ad libitum till 7 weeks and then severely restricted to reach standard BW by 21 weeks. Parameters measured included BW, uniformity, age at Sexual Maturity (SM), total and settable egg production, body composition, liver size and composition, in vitro Lipogenesis (IVL) and Heterophil-Lymphocyte ratio (H/L). Breeder production performance was evaluated through 45 weeks of age. Birds fed ED grew more efficiently than SK or SLOW. The BROIL treatment resulted in significantly worse feed utilization than all other groups. Frame size was consistently greater in BROIL pullets and consistently smaller in SLOW pullets. Birds fed ED reached SM before SK, who in turn reached SM before SLOW or BROIL birds. Egg production was significantly higher in ED than SK, which in turn was higher than either SLOW or BROIL. The difference of nearly 17 total eggs per hen between ED and BROIL hens could not be explained by differences in BW or body composition. Liver weight and IVL was elevated in SK and SLOW pullets above ED pullets during rearing. Liver weight and IVL were lower in BROIL pullets than other groups during rearing, but after photostimulation dramatic increases in liver weight and IVL resulted in this trend being inverted by 27 weeks. As an indicator of stress, H/L ratios were elevated above ED pullets in SK, SLOW and BROIL pullets at various times during rearing. These times generally coincided with the periods of most severe feed restriction. Feeding regimens and growth curves have a major influence on efficiency and reproductive performance in broiler breeders. These effects were not attributable solely to differences in BW and body composition. The depression of IVL in broilerized pullets even after restricted feeding was implemented was of great interest and warrants further examination.